Imagery intervention to increase flow state and performance in competition - Koehn, S.; Morris, T.; Watt, A. P. (The Sport Psychologist, 2014)
The purpose of this study was to examine the effectiveness of an imagery intervention for enhancing the experience of flow state and performance in junior athletes. On the basis of previous results, a tailored imagery script was developed to target critical flow dimensions, namely challenge-skills balance, clear goals, concentration on the task, and sense of control. It was hypothesized that the use of cognitive and motivational imagery would increase specific flow dimensions, which, in turn, would enhance flow state and competition performance. Participants in a single-case, multiple baseline A-B design study were four nationally ranked athletes. Following a 6-week baseline phase monitoring flow state and performance and a 6-week intervention phase using relaxation in conjunction with imagery techniques, three participants showed a sustained increase in flow experiences, and all four participants improved their service performance, groundstroke performance, and ranking-list position.